Development of Interactive E-Modules Assisted by The Kvisoft Flipbook Maker Application on Algebraic Forms Grade VII - Fachrunisa, Ainun; Kuncoro, Krida Singgih; Arigiyati, Tri Astuti (Universitas Sebelas Maret, 2022)
The research objectives are to develop a mathematics learning media product that can be accessed via android with the help of the Kvisoft Flipbook Maker application. The type of research is Research and Development (R&D) with a 4-D Thiagarajan research model which consists of 4 stages (Define, Design, Development, and Disseminate). The subjects of this study were 10 students of class VII SMP N 3 Bantul. Data collection techniques were performed through questionnaires and validation sheets. Based on the results of expert validation, the e-module-based learning media is feasible to be used in the mathematics learning process and is included in the very good category with an ideal percentage of 90.85%. The results of the response of educators with the ideal percentage of 87.5% in the excellent category while the results of the responses of students with the ideal percentage of 92% in the excellent category. This shows that the learning media developed is suitable for use in the mathematics learning process and e-module-based media products can be further developed in the learning process to encourage educators to be more creative and innovative in creating interesting and fun media for students.